Immunohistochemical localization of calcitonin gene-related peptide and cotransmitters in a subpopulation of post-ganglionic neurons in the porcine inferior mesenteric ganglion - Majewski, Mariusz; Heym, Christine (Acta histochemica, 1992)
Applying double-fluorescence immunohistochemistry, adrenergic and non-adrenergic postganglionic sympathetic neurons, in the porcine inferior mesenteric ganglion (IMG) are subdivided according to size and cotransmitter content. Calcitonin gene related peptide (CGRP)-immunoreactive (IR) neurons are demonstrated to belong to the non-adrenergic, i.e. tyrosine hydroxylase- and DOPAmine-ß-hydroxylase-(DßH)-negative subpopulation of postganglionic perikarya. Virtually all of the CGRP-IR postganglionic neurons exhibit colocalization with somatostatin (SOM), and, some of them with neuropeptide tyrosine (NPY). Additionally, NPY-, SOM-, and NPY/SOM-IR subpopulations of adrenergic and non-adrenergic neurons are observed. CGRP-immunoreactivity is seen in dense networks of intraganglionic varicose nerve fibres, adjacent to the TH-and SOM-IR neurons. NPY-IR perikarya are sparsely supplied by CGRP-IR fibres. SOM- and NPY-IR nerve fibres also exist in the inferior mesenteric ganglion. The functional relevance of CGRP-IR postganglionic neurons, as well as target organs of these neurons remain to be elucidated.
Elektronische Reproduktion der Druck-Ausgabe 20. Februar 2012
Gesehen am 06.11.2025